(untitled) (Gaceta Técnica, 2023)
The purpose of this work is to describe, through a critical analytical monographic study, how the Diagram as an instrument of graphic representation becomes the cartography of the design process. The information was collected in the field, and organized in a population made up of the number of students present in the author Design workshops, in a period of 5 regular academic semesters. This occurs in a context where the teaching of architecture has been distinguished with characteristics for understanding the Architectural Object as a final product, its dissection into parts, and as a representation of a response to a design problem. This attitude could lead to dissipating attention from important moments where knowledge is collected and recorded, as well as particular experiences. Added to this is the fact that in the process of synthesis and definition of the final Architectural Object, the architectural project is ignored as a complex whole